2019
DOI: 10.1007/s41095-019-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modified adaptive k-means segmentation algorithm

Abstract: Segmentation is the act of partitioning an image into different regions by creating boundaries between regions. k-means image segmentation is the simplest prevalent approach. However, the segmentation quality is contingent on the initial parameters (the cluster centers and their number). In this paper, a convolution-based modified adaptive k-means (MAKM) approach is proposed and evaluated using images collected from different sources (MATLAB, Berkeley image database, VOC2012, BGH, MIAS, and MRI). The evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Most of the performance metrics encountered in the review include area under curve (AUC), sensitivity (Sn), specificity (Sp), accuracy (Acc), precision (P), recall (R), positive predictive values (PPV), Matthews correlation coefficient (MCC), geometric mean (G-Mean), which are usually successful in describing the classification performance [ 8 , 9 ]. Performance measures including Dice similarity coefficient (DSC) or Zijdenbos similarity index (ZSI) or F1-score, Hausdorff distance (H) and intersection over union (IoU) are the most effective metrics for measuring system’s segmentation performance [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the performance metrics encountered in the review include area under curve (AUC), sensitivity (Sn), specificity (Sp), accuracy (Acc), precision (P), recall (R), positive predictive values (PPV), Matthews correlation coefficient (MCC), geometric mean (G-Mean), which are usually successful in describing the classification performance [ 8 , 9 ]. Performance measures including Dice similarity coefficient (DSC) or Zijdenbos similarity index (ZSI) or F1-score, Hausdorff distance (H) and intersection over union (IoU) are the most effective metrics for measuring system’s segmentation performance [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Region-based segmentation technique was in use in medical image analysis until the deep learning approach evolved in the field of computer vision [ 8 ]. However, Lee et al [ 7 ] in their survey paper indicated that the existence of deep learning in the research community has become a reason to use object recognition in an image.…”
Section: Deep Learning In Tumor Detection Segmentation and Classificationmentioning
confidence: 99%
“…Regionbased methods gather similar regions together according to the geometric information of the mesh. Well-known region-based works include K-means [16,17], clustering [18], hierarchical decomposition [13], primitive fitting [19], watersheds [20], random walks [21]. Boundary-based methods instead detect the geometric feature boundaries of the mesh which divide the mesh into different parts.…”
Section: General Mesh Segmentationmentioning
confidence: 99%
“…In the practical application, to meet our needs, it is sometimes necessary to use multidimensional threshold segmentation methods or select multiple thresholds at the same time to achieve effective segmentation of the target grayscale image. As the number of grayscale image information dimensions or the number of selected thresholds increased, the computational complexity of the threshold segmentation algorithm increases rapidly [3]. It will take a long time, which to a certain extent limits the use of segmentation algorithms.…”
Section: Introductionmentioning
confidence: 99%